The Fourth Energy Transition and the European Energy Crisis: Lessons for the EAEU - Z. V. Sergeeva (Евразийская интеграция: экономика, право, политика)
Over the recent decade many developed countries took a new energy policy course, substituting fossil fuels with renewable energy sources (RES). The main driver behind it is the aspiration to achieve carbon neutrality by mid-century to prevent climate change. This trend was called “the fourth energy transition”. However, the European energy crisis that took place in September 2021 shows that such policies lead to a deadlock due to the lack of technological readiness to provide stable functioning of the energy system based only on renewable energy. Moreover, the politics of abandoning of fossil fuels results in a suboptimal outcome — use of energy resources with a higher carbon footprint (coal), which appear to be more price affordable during the crisis than natural gas. Recently, an increasing number of studies have appeared emphasizing the need for the Eurasian Economic Union countries to transition to a “green” economy. Analyzing the EU energy crisis, this paper attempts to propose an alternative way of sustainable development for the EAEU, which allows to ensure its energy security and is based on the use of carbon-neutral versions of traditional energy sources.Aim. The aim of this research is to analyze the economic consequences of the overreliance on RES for the European energy market.Tasks. The study has the following objectives.To analyze the causes and course of the energy crisis of 2021 on the example of the EU countries and the UK.To identify the consequences of the energy crisis for the EU countries and the UK.To propose a solution to avoid the energy crisis in the EAEU countries.Methods. Using a case study method and market data (TTF, Rotterdam coal and France power month ahead futures’ prices), the researchers demonstrate that rejection of hydrocarbons can lead to irreversible negative consequences for the energy system, especially with the absence of enough storage options.Results. The data presented casts doubt on Europe’s readiness to achieve both zero-emission targets by 2050 and intermediate targets such as a 55% reduction in greenhouse gas emissions from 1990 levels by 2030. There are many questions about the prospects of the fourth energy transition - in its current form, its principles threaten existing energy systems without offering a reliable alternative.Conclusions. The article concludes with a suggestion for policymakers to achieve climate goals with economically viable carbon-neutral versions of conventional hydrocarbon products (such as liquefied natural gas and oil).